High Appendicitis Incidence in Young Adults Calls for Routine Histological Examination: Tingginya Insiden Usus Buntu pada Orang Dewasa Muda Memerlukan Pemeriksaan Histologi Rutin - Zainab Khairullah Aouda; Ahmed Aziz Ahmed; Dmoaa Majid Nasar (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the histopathological changes associated with appendicitis in appendicectomy specimens from Nasiriyah General Hospital. Employing a retrospective analysis on twenty specimens, it aims to underscore the importance of routine histological examinations. Findings reveal that all specimens were afflicted with appendicitis, featuring notable occurrences of mucosal glandular hyperplasia (43%), mucosal and submucosal layer necrosis (42%), and severe inflammatory cell infiltration (71%). These results highlight the necessity of comprehensive histological assessments in appendicectomy specimens to enhance diagnostic accuracy and improve patient management, particularly among adolescents and young adults. Highlights: All specimens confirmed appendicitis with significant alterations. Routine histological exams critical for accurate diagnosis. Enhanced scrutiny improves adolescent, young adult treatment. Keywords: Appendicitis, Histopathological Changes, Appendicectomy, Histological Examination, Adolescents